2019
DOI: 10.1001/jamacardio.2019.3649
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Thromboembolic Risk in Patients With Postoperative Atrial Fibrillation After Left-Sided Heart Valve Surgery

Abstract: IMPORTANCE New-onset postoperative atrial fibrillation (POAF) is a common complication of cardiac surgery. However, data on the long-term risk of thromboembolism in patients who develop POAF after heart valve surgery are conflicting. In addition, data on stroke prophylaxis in this setting are lacking.OBJECTIVE To assess the long-term risk of thromboembolism in patients developing new-onset POAF after isolated left-sided heart valve surgery relative to patients with nonsurgical, nonvalvular atrial fibrillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…[1][2][3][4][5] While usually self-limiting, anticoagulation is recommended for patients with recurrent or persistent AF after CABG, as the thromboembolic risks of POAF are similar to that of nonsurgical AF. [6][7][8][9] The ICU length of stay was longer for patients randomized to receive apixaban (2.14 versus 1.43 days, P ¼ .016; Table 2). This may have been due to significantly more patients having a history of myocardial infarction in the apixaban group (17 vs 9 patients, P ¼ .032).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] While usually self-limiting, anticoagulation is recommended for patients with recurrent or persistent AF after CABG, as the thromboembolic risks of POAF are similar to that of nonsurgical AF. [6][7][8][9] The ICU length of stay was longer for patients randomized to receive apixaban (2.14 versus 1.43 days, P ¼ .016; Table 2). This may have been due to significantly more patients having a history of myocardial infarction in the apixaban group (17 vs 9 patients, P ¼ .032).…”
Section: Discussionmentioning
confidence: 99%
“…6 Despite the normally limited duration of POAF, it carries similar thromboembolic risk as nonsurgical, nonvalvular AF. [7][8][9] When anticoagulation is needed, warfarin therapy has been the mainstay of therapy for patients with POAF after cardiac surgery and is generally less expensive than newer directacting oral anticoagulants (DOAC). However, warfarin therapy involves international normalized ratio (INR) monitoring, dose adjustment to maintain therapeutic range, and substantial drug and food interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This presumption is clearly incorrect, and it is possible that recurrent AF following discharge portends a greater risk of stroke or systemic thrombo-embolism. Recent trials have shown oral anticoagulation after discharge can reduce thromboembolic events in patients with post-operative AF after valve surgery (HR 0.45) [21] , and for secondary AF following infection [3] . This highlights the potential use of oral anticoagulation in patients with secondary AF, to reduce risk of stroke and premature death, presuming that AF episodes are identified during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Butt et al showed in a cohort of patients with left-sided valvular surgery that POAF patients were similarly likely to be initially treated with oral anticoagulants compared with new-onset nonvalvular atrial fibrillation (NVAF) patients, but POAF patients were less likely to still be taking oral anticoagulants at 1 year compared with NVAF patients. 84 Though they were less likely to be on oral anticoagulants at 1 year, patients with POAF had similar risk of thromboembolism as NVAF (HR: 1.22; 95% CI: 0.88-1.68). This similar thromboembolic risk is not mediated by recurrent AF, as POAF patients after all types of cardiac surgery had lower risk of recurrent AF compared with NVAF (HR: 0.62; 95% CI: 0.56-0.70), but the subset of patients who underwent mitral valve surgery had similar risk of recurrent AF when compared with NVAF patients.…”
Section: Secondary Preventionmentioning
confidence: 95%
“…This similar thromboembolic risk is not mediated by recurrent AF, as POAF patients after all types of cardiac surgery had lower risk of recurrent AF compared with NVAF (HR: 0.62; 95% CI: 0.56-0.70), but the subset of patients who underwent mitral valve surgery had similar risk of recurrent AF when compared with NVAF patients. 84 While this discrepancy between rates of recurrent AF and thromboembolism may represent subclinical short AF events, it is not clear why subclinical events would not be equally prevalent in both groups. It is therefore possible that POAF indicates the presence of an atrial cardiopathy that itself increases thromboembolic risk.…”
Section: Secondary Preventionmentioning
confidence: 99%